Heutagogy as a framework for Christian discipleship: the triadic role of biblical wisdom literature, the teachings of Jesus Christ, and the work of the Holy Spirit - Hukkinen, Esa (Journal of Religious Education, 2025)
Heutagogy—also known as self-determined learning—empowers individuals to take charge of their personal growth by fostering proactive approaches to self-development. In a Christian context, self-enacted spiritual growth can operate within a range of personal, denominational, and/or hermeneutical understandings of discipleship. Moreover, self-determined learning transcends diverse Christian traditions, mirroring different expressions of the role and work of the Holy Spirit in capacitating Christian discipleship. This conceptual paper contributes to the literature by expounding and advocating heutagogy as an under-appreciated framework for facilitating spiritual growth. To construct its argument, the paper draws on three sources: biblical wisdom literature, the teachings of Jesus Christ, and selected expressions of the continuing work of the Holy Spirit in the lives of Christian believers.